Soul surfer : a true story of faith, family, and fighting to get back on the board - Hamilton, Bethany; Berk, Sheryl; Bundschuh, Rick, 1951- (New York : Gallery Books : MTV Books, 2011)
The teenage surfer who lost her arm in a shark attack in 2003 describes how she has coped with this life-altering event with the help of her faith, the changes in her life, and her return to the sport she loves.
Originally published: New York : Pocket Books ; MTV Books, c2004.
Includes interviews with main parties involved in the Soul Surfer movie.
Keywords: Hamilton, Bethany -- Juvenile literature; Hamilton, Bethany; Surfing -- Wounds and injuries -- Biography; Shark attacks -- Hawaii -- Kauai -- Personal narratives -- Juvenile literature; Amputees -- Biography -- Juvenile literature; Amputees -- Rehabilitation -- Juvenile literature; Surfing -- Biography; Amputees; Amputees -- Rehabilitation; Shark attacks